Uma abordagem teórica e experimental do oscilador harmônico em duas dimensões utilizando as curvas de Lissajous - Cena, Cícero R. (2014)
The study of oscillatory phenomena is an important topic in several areas of knowledge. The understanding and the solution of many problems that scientists and engineers confront nowadays can be formulated, at least as an analogy, in terms of an oscillatory movement. The description of the motion of this nature has remarkable contributions to the mathematical and conceptual formation of the students and for solving daily problems in several areas. In this paper we propose a theoretical and experimental approach involving the phenomenon of harmonic oscillations in two dimensions. Lissajous curves were used as experimental demonstration of the resulting trajectories. These curves were obtained from relatively simple experimental apparatus, which is affordable in most teaching laboratories of physics. © Sociedade Brasileira de Física.